Mother: A Story - Norris, Kathleen Thompson, 1880-1966 (Salt Lake City, UT : Project Gutenberg, 2003)
"Mother: A Story" by Kathleen Thompson Norris is a novel likely written in the early 20th century. The narrative revolves around Margaret Paget, a young teacher who grapples with her ambitions and the mundane challenges of her life in a small town, particularly as she contemplates the contrast between her responsibilities and her personal aspirations. The story captures the dynamics of family life, societal expectations, and the struggle for self-fulfillment. At the start of the book, we are introduced to Margaret as she reflects on her weary existence amid dreary weather on the last week of school. She is surrounded by the mundane realities of teaching, feeling exhausted and yearning for a life beyond the confines of her classroom. Margaret communicates her frustrations to her colleague, Mrs. Porter, revealing her dissatisfaction and longing for something more than the monotonous routines that dictate her life. The situation intensifies when news of her brother's heartbreak over a friend's engagement prompts her to confront the societal pressures she faces as a woman in her position. As the chaos of family life unfolds, including the arrival of her loving yet wearied mother, Margaret's desire for change and opportunity becomes palpably clear, setting the stage for her eventual transformative journey. (This is an automatically generated summary.)
Release date is 2003-01-01
Produced by Joyce Noverr and Jim Weiler. HTML version by Al Haines.
Keywords: Self-sacrifice -- Fiction; Families -- Fiction; Mothers -- Fiction; Love, Maternal -- Fiction; Self-confidence -- Fiction